Bariatric surgery and LDL cholesterol (BASALTO) trial study protocol: randomised controlled study evaluating the effect of gastric bypass versus sleeve gastrectomy on high LDL cholesterol - David Benaiges; Albert Goday; Juana A Flores-Le Roux; Montserrat Fitó; Oscar Pozo; Jose Rodríguez-Morató; Carme Serra; Manuel Pera; Gemma Llauradó; Elisenda Climent; Olga Castañer; Jose M Ramon; et al. (BMJ Open, 2020)
Introduction Observational studies have shown gastric bypass to be superior to sleeve gastrectomy in terms of low-density lipoprotein (LDL) cholesterol improvement. If these results are confirmed in randomised controlled trials, presurgical LDL cholesterol status could be a relevant factor in surgical procedure election. Furthermore, it is also necessary to establish the mechanisms by which LDL cholesterol improves after surgery and whether qualitative and quantitative changes occur in the different lipoprotein subclasses. The first objective is to ascertain whether high LDL cholesterol levels before surgery can be considered an additional factor when selecting the most appropriate surgical procedure for each patient (gastric bypass or sleeve gastrectomy). Hence, the 1-year remission rates of high LDL cholesterol after gastric bypass and sleeve gastrectomy in patients with morbid obesity will be compared. Secondary objectives were (1) to compare changes in other lipoproteins and LDL composition and (2) to study the pathophysiologic mechanisms related to LDL cholesterol remission.Methods and analysis A randomised clinical trial, with intention-to-treat analysis, will be conducted to compare LDL cholesterol remission between gastric bypass and sleeve gastrectomy, with a 12-month follow-up. Inclusion criteria will be patients between 18 and 60 years of age with body mass index ≥40 kg/m2 or ≥35 kg/m2 with significant obesity-related comorbidity and high LDL cholesterol levels. Patients will be evaluated preoperatively and at 3, 6 and 12 months after bariatric surgery. Examinations will include routine blood chemistry, anthropometric measurements, food intake recall, physical activity questionnaires and serum samples for lipidomic and lipoprotein characterisation.Ethics and dissemination Ethics approval has been granted by the Parc de Salut Mar Ethics Committee (2019/8471/I). The study and its conclusions regarding the primary and secondary objectives will be presented as manuscripts submitted for peer-reviewed journal publication.Trial registration number NCT03975478.